Risk of New-Onset Diabetes after Transplantation among Kidney Transplant Recipients with Cytomegalovirus Infection: A Retrospective Analysis - Muhammad Tassaduq Khan, Rashid Bin Hamid, Naranjan Lal (Pakistan Journal of Medical & Health Sciences, 2022)
Background: New-onset diabetes after transplantation (NODAT) is one of the common complications reported in patients with kidney transplant and is associated with risk of infection, poor allograft and patient survival. There is conflicting research literature regarding the role of cytomegalovirus (CMV) infection in increasing the risk of NODAT development. Objective: To assess the risk of development of NODAT in kidney transplant patients with CMV infection Methods: A total of 59 kidney transplant patients were studied from March 2017 to February 2019. NODAT was defined as two readings of fasting plasma glucose of ≥126 mg/dL at three months post-transplant. CMV viral load was also documented. The 12 months post-transplant allograft and patient survival outcomes were also measured. Results: Mean age was 43.4 ± 6.2 years. Nearly one-fourth, 14 (23.7%), of the patients had NODAT. CMV viral load and viremia were high in NODAT group; however, the result did not reach statistical significance. CMV DNA replication was statistically high during 1-6 months post-transplant for NODAT group (P<0.001). Only 7 (11.9%) recipients advanced to symptomatic CMV infection. Also, we found that high CMV viremia load was associated with poor kidney allograft function at 12 months. Conclusions: In summary, this study showed that infection with CMV may not be a risk factor to develop NODAT in patients transplanted with kidney. An elevated CMV viral load may decrease the post-transplant allograft function at 12 months. The prompt diagnosis and timely management of CMV infection could substantially lessen the risk to develop NODAT subsequent worsening of allograft and patient survival.